Determining Language Proficiency Levels in Preschool Teachers in Cartago: A University Extension Activity Funded by Law 9829 - Vallecillo Alfaro, Johanny (2025)
This article presents the findings of the extension activity CF1470016, funded under the Cement Law Call No. 9829 and executed by the School of Language Sciences of the Costa Rican Institute of Technology. The main objective was to determine the English language proficiency level of preschool teachers in five cantons of Cartago by applying the Oxford Test of English (OTE). With a quantitative descriptive design, a diagnostic survey and the OTE were applied to a purposive sample of 31 teachers who lacked prior certification. Familiarization and socioemotional support sessions were also implemented. The results show that 67% of the participants scored between A2 and B1 of the CEFR; reading comprehension reached the highest scores (some at B2), while writing revealed the greatest need for further training. Implications for continuing education are discussed, and a replicable model for teacher certification is proposed.